The Implementation of Blind Signature in Digital Cash - Hariandi Maulid (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2015)
Digital cash, an electronic or digital simulation of real cash, has been used widely to buy or sell goods in the recent internet society. As it circulates via internet, all information regarding transaction using digital cash can be recorded. Hence, the anonimity and privacy become a serious concernto the payer and the payee. This paper will discuss how the implementation of blind signature can preserve the anonimity and the privacy of all digital cash user.